PENGARUH KEPEMIMPINAN, MOTIVASI, DAN DISIPLIN KERJATERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI MEDIASI (STUDI PADA KOPERASI SIMPAN PINJAM BANGUN JAYA JAWA TENGAH ) - Putra Satya Nugraha, 12.42.02.0086; Sholiha, Euis (Jurnal Mahasiswa Pasca Sarjana, 2015)
This research analyzes theinfluence of leadership, motivation andworkdidiplinon the performance oftheemployeesjob satisfactionasmediationstudiesoncredit unionBangunJayaSemarang. The population inthis studyis theEmployeesCooperativeCreditBangunJayasemarang.sejumlahsave100 people. Datawere collectedusing a questionnaire, after whichthe datawere processed usingSPSS19.Testinstrumentsincludevalidity,reliability, testmodels, test the coefficientof determinationandhypothesis testing. The results showedthat theleadershipdoes notaffect the performance, motivationaffect the performance,affect the performance ofwork discipline, leadership does notaffect thesatisfaction, motivationand disciplineaffect thejobsatisfactioneffect onjob satisfaction. While the viewsof themediationtestfoundthatsatisfaction does notmediatethe effect ofleadershipon the performance, fromthe influence of motivationon the performanceshowedthat job satisfactionintomediation, and job satisfactionare alsomediatesthe influence oflabor disciplinetoperformance.Keywords: Leadership, Motivation, Work Discipline, Performance andJob Satisfaction Â